Eupomatia laurina R. Br. fruit solvent extractions inhibit the growth of a panel of pathogenic bacteria - Bryant, Krystal; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Eupomatia laurina are trees native to Australia and Papua New Guinea. The fruit of this species are consumed as a bushfood. Infusions and decoctions produced from leaves and bark have reputed antiseptic properties and were used traditionally to treat a variety of bacterial diseases. Despite this, E. laurina fruit solvent extractions have not been rigorously examined for antibacterial properties against many pathogens. Methods: The antimicrobial activity of E. laurina fruit solvent extractions was inves- tigated by disc diffusion and growth time course assays against a panel of pathogenic bacteria. The growth inhibitory activity was quantified by MIC determination. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: Methanolic and aqueous E. laurina fruit extracts inhibited the growth of a wide range of bacterial species. Growth of both gram positive and gram negative bacteria was inhibited by the E. laurina fruit extracts to approximately the same extent. With some noteable exceptions, the methanolic extracts were generally more potent than the aqueous extracts. The methanolic and aqueous E. laurina fruit extracts were particularly potent inhibitors of P. mirabilis growth, with MIC values as low as 83 µg/mL (aqueous extract against the P. mirabilis clinical isolate). The antibacterial activity of the methanolic E. laurina fruit extract was further investigated by growth time course assays which showed significant growth inhibition in cultures of K. pneumoniae and P. mirabilis within 1 h of exposure. All extracts were determined to be nontoxic in the Artemia franciscana nauplii bioassay, indicating their safety for internal use as well as for topical uses. Conclusions: The lack of toxicity of the E. laurina fruit extracts and their growth inhibitory bioactivity against a panel of patho- genic bacteria partially validate the traditional usage of these species to treat bacterial diseases and indicate their potential in the development of antiseptic agents.
Keywords: Eupomatia laurina; Eupomatiaceae; Native guava; Copper laurel; Australian plants; Antibacterial activity; Medicinal plants.